Address Presenting the Second Annual Report of the International Bank - McCloy, John J. (Washington, DC: World Bank, 2019)
John. J. McCloy, President of the International Bank for Reconstruction and Development, discussed staff recruitment and the development of Bank policies. Loan requirements emphasize productive projects of reconstruction and development. Supervision ensures the funds are not diverted. He spoke of the need for balanced budgets, sound tax systems, and monetary stability. The Bank is in a position to help facilitate financial reforms. McCloy has been in close contact with the American investment community as the Bank floated its first bond issue. He highlighted the need to gain access to currencies of other member countries. He noted the relationship of Marshall Plan aid to Bank activities. Despite the discouraging economic situation, he believes the Bank has made real progress in repairing the damage from the war. The best hope for the future lies in the magnitude of development potential of the Bank’s members.